Independence, history and law - Uribe Ángel, Jorge Tomás (Universidad Pedagógica y Tecnológica de Colombia, 2011)
The article, within the paradigm of colonial modernity, begins to investigate the signiicance of history taking for the generation of Independence and goes back to examine the role that corresponded to the trend of so-called historical constitutional claims raised in the Creole in response to the crisis created in Spain since 1808. Emphasizes the worship of the natives to the law, and includes the Colombian constitutional tradition, which is inscribed, as in the rest of Latin America, lack of commitment to history and the adoption of models from elsewhere, especially France and the United States. Finally, a relection on the possible adoption of the “coloniality of remembering.”